Examining the Relationship between EFL Students' OSEL and Their Achievement - Shafira Stasya; Ive Emaliana (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: The purpose of this study is to examine the correlation between EFL student’s online self-regulated (OSEL) and the achievements of senior high school students in Malang, Indonesia. The subject of this study were 136 EFL students of a senior high school in Malang, Indonesia with the use of two instruments: the online self-regulated learning questionnaire (containing five dimensions of OSEL; Goal Making, Environmental Construct, Task Approach & Time Management, Help-Seek, Self - Evaluation) and the mid-term test scores. Methodology: The Pearson product-moment correlation is used to analyze the data and further verifies that students OSEL strongly correlates to their achievements while undertaking online learning. Findings: It was reported that the higher the OSEL, the better they achieve. For example, students who have high achievement test scores agree that finding someone knowledgeable in online learning is an excellent solution to solve online learning difficulties. However, since technical and individual obstacles that students encounter could be the challenge, the role of teachers are essential in helping students overcoming them. Conclusion: The results of this correlation provide prediction towards pedagogical implications related to successful teaching-learning process, teacher professionalism, and maintaining a high quality school.